2020
DOI: 10.3389/fenrg.2020.00004
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Thick Organic Pigment Layer Up to 10 μm Activated by Crystallization in Organic Photovoltaic Cells

Abstract: Organic optoelectronic devices tend to have limited thickness. Organic light emitting diodes (OLED) and organic photovoltaic cells (OPV) made of organic pigments are typically with thickness of a few or a few tens of nanometers. Thickness of organic photovoltaic cells made with polymers exceeds them typically up to the order of a few 100 nm but still necessarily co-optimized with respect to light absorption and charge transport. Here, we demonstrate that crystallization made a 10-µm-thick pigment layer active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
(61 reference statements)
0
8
0
Order By: Relevance
“…One exception to this notion is if new processing parameters are found that fundamentally alter the deposition kinetics. [58] Finally, when comparing the mobilities of different systems it is important that 1) the same characterization method is applied for all systems since different techniques yield different values for the mobility, [59] and 2) the applied method is reliable. Here, photo-CELIV [47,48] or OTRACE [43] are good candidates, whereas, for example, SCLC measurements are prone to errors.…”
Section: Classification Of Materials Systemsmentioning
confidence: 99%
“…One exception to this notion is if new processing parameters are found that fundamentally alter the deposition kinetics. [58] Finally, when comparing the mobilities of different systems it is important that 1) the same characterization method is applied for all systems since different techniques yield different values for the mobility, [59] and 2) the applied method is reliable. Here, photo-CELIV [47,48] or OTRACE [43] are good candidates, whereas, for example, SCLC measurements are prone to errors.…”
Section: Classification Of Materials Systemsmentioning
confidence: 99%
“…It has been reported that in a 10-μm-thick ZnPc:C 60 OPV sample grown by using the same method as in this study, a needle-like structure was observed by SEM on the cracked sample surface . However, the sample observed in the previous study is different from the present study because phthalocyanine included metal Zn, and the thickness was very thick.…”
Section: Resultsmentioning
confidence: 99%
“…The substrate temperature was 70 °C, and the deposition rates of C 60 and H 2 Pc were 1.0 and 1.4 Å/s, respectively. To control the interfacial structure of the device and obtain a highly ordered BHJ, we used polydimethylsiloxane (PDMS) as a co-evaporant component with an evaporation rate of 0.35 Å/s. The electron microscopy samples were prepared in two ways: The SEM samples were obtained by cutting a glass plate with an indium tin oxide (ITO) electrode by using a diamond glass cutter, and the cross sections were then observed.…”
Section: Methodsmentioning
confidence: 99%
“…Conjugated organic compounds, due to their tunable optical and electronic properties, have become promising materials for applications in devices such as field effect transistors [1][2][3], photovoltaic cells [4][5][6][7][8], light-emitting diodes [9][10][11][12][13], sensors [14][15][16], and others. Understanding the relationship between the structure and optoelectronic properties of organic semiconductors is essential when designing the architecture of the above-mentioned devices in order to achieve their optimal parameters, including high efficiency [17].…”
Section: Introductionmentioning
confidence: 99%